Enactors or reactors? Work-life border management for women in law in Nigeria - Beauregard, T. Alexandra; Adisa, Toyin Ajibade (Community, Work and Family, 2021)
Work-family border theory casts individuals as protagonists who are enactive rather than reactive in shaping borders between work and personal life domains. To what extent is this the case in strongly patriarchal contexts that constrain women’s personal agency? This qualitative study conducted with 32 female lawyers, magistrates and justices in Nigeria shows how participants engage in new border management tactics in response to context-specific institutional and social factors. Faced with public harassment and physical assault in a country where violence against women is normalised, female legal professionals restructure family borders to extend no further than their homes and retain police attachés as border-keepers. When their families are reconfigured via nonconsensual polygamous marriages, women’s work borders are strengthened by co-wives performing domestic labour and family borders are strengthened by co-wives’ assistance with job tasks, thereby reducing participants’ work-family conflict. Rather than strategically enacting work-life borders within known situational constraints, Nigerian female legal professionals react to involuntary events that limit their agency to negotiate desired work and personal lives. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; conciliation famille-travail; famille; intersectionnalité; maternité; nigeria; patriarcat; polygamie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

Cuidado em território de exclusão social: covid-19 expõe marcas coloniais - Camilo, Claudia; Kahhale, Edna; Ferreira, Maria Luísa; Schveitzer, Mariana (Saúde e Sociedade, 2021)
A intersecção de gênero, raça e classe marca os territórios de exclusão social, especialmente em um país que carrega cicatrizes da colonialidade patriarcal e capitalista em suas estruturas, como é o caso do Brasil. O objetivo deste trabalho é compreender o cuidado em um desses territórios: a cidade de Cubatão/SP. A investigação, feita entre 2017 e 2020, incluiu a pandemia da covid-19, que sobrecarregou o cuidado no território. O método foi a pesquisa qualitativa, com oficinas, observação participante e entrevistas de profundidade. O cuidado era majoritariamente oferecido por mulheres, líderes comunitárias e profissionais da atenção primária do Sistema Único de Saúde. Para analisar os dados, utilizou-se a hermenêutica de profundidade. O referencial teórico foi a costura das teorias feministas da ética do cuidado, ecofeministas e interseccionais. A pesquisa revelou diversos desafios e potencialidades, como o cuidado ético-político, eixo da busca por justiça socioambiental. , Abstract The intersection of gender, race and class marks the territories of social exclusion, especially in a country that carries scars of a patriarchal and capitalist colonialism in its structures, as is the case in Brazil. The objective was to understand care in this territory of exclusion in Cubatão, São Paulo, Brazil. The research, conducted between 2017 and 2020, included the pandemic of COVID-19, which overloaded care in this territory. The method was qualitative research, with workshops, participant observation and in-depth interviews. The care delivered by community leaders and primary health care professionals from the Brazilian National Health System was mostly performed by women. For data analysis, depth hermeneutics was used. The theoretical reference was the perspective of feminists: ecofeminist, intersectional and Care Ethics. The study showed several challenges and the ethical-political care as an axis in the search for social and environmental justice.
http://www.scielo.br/scielo.php?script=sci_arttext&pid=S0104-12902021000200202&tlng=pt
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; brésil; care; covid-19; intersectionnalité; pandémie; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; travail; écoféminisme

Hidden in plain sight: Uncovering the emotional labor of Black women students at historically White colleges and universities. - Kelly, Bridget T.; Gardner, Paige J.; Stone, Joakina; Hixson, Ashley; Dissassa, Di-Tu (Journal of Diversity in Higher Education, 2021)
We utilized the emotional labor triangle to understand how 16 Black women students who attended Historically white colleges and universities (HWCUs) navigated gendered-racialized oppressive environments that mattered to their academic success. This study contributes to a gap in the literature, as much of the research focused on students of color without disaggregating for gender or other social identities. In addition, the literature is scant on experiences of Black women students use of emotional labor. Emotional labor has largely been studied from a management perspective. Through qualitative semi-structured interviews, we examined the emotional labor Black women expended while pursuing their undergraduate degree. We employed a qualitative, intersectional, methodological approach to foreground historically marginalized voices and situated the study in the hypervisibility Black women participants described feeling as space invaders on their historically White undergraduate campus and at the same time the invisibleness of their voice and masking of their feelings as they encountered gendered racism. Further, we emphasized the emotional toll and stress that may occur for Black women when they do not utilize engaged coping mechanisms while expending their emotional labor. The study holds implications for educators to address emotional labor inequities within HWCUs. (PsycInfo Database Record (c) 2021 APA, all rights reserved) © 2019 National Association of Diversity Officers in Higher Education
Number: 2
Keywords: amériques; approches et analyses; care; colère; femmes universitaires noires*; intersectionnalité; projet charge mentale; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail émotionnel; violences; états-unis

Gendered care work and environmental injustice: A feminist analysis of educator's emotional labor in disaster recovery - Shtob, Daniel A.; Petrucci, Larissa (Environmental Justice, 2021)
Although environmental justice researchers have long been interested in the connections between disaster recovery, gender, and home- and community-based care, the consequences of the post-disaster performance of emotional labor by workers in care occupations have largely gone unnoticed. To address this gap in the environmental injustice literature, in this exploratory article we employ a feminist analysis of firsthand accounts of elementary educators' professional and personal experiences caring for their students in the Florida Keys after Hurricane Irma. We find that caring labor was increasingly necessary in the post-disaster context, both inside and outside the classroom. Teachers and other care professionals in feminized occupations may, therefore, perform an emotional double duty, supporting their students' emotional needs while also contending—as working- and middle-class individuals—with the personal consequences of disaster. We suggest that these educators may bear an unrecognized and undercompensated disproportionate burden at the intersection of class and occupational status. Because of this, we introduce an underexplored component to the racialized disaster patriarchy and intersectional disaster research: feminized occupational status. Inspired by environmental justice research legacies developed in the wake of earlier Gulf Coast disasters, we draw attention to the contributions of these absolutely essential recovery workers and how they may experience environmental injustice even as they contribute to others' recovery. Our goals are to promote recognition and fair distribution of burdens, encourage research into the contours of environmental justice and care work, and support the development of more just planning, training, and compensation regimes.
Keywords: amériques; approches et analyses; care; discipline; floride; intersectionnalité; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; émotions

Quadruple défi pour les artistes femmes, immigrantes et allophones : le cas du premier Sarau das Minas Montréal - Vasconcellos de Carvalho, Dalila (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Cet article porte sur le processus de création du premier Sarau das Minas Montréal : une soirée de sororité artistique qui s’est déroulée le 8 mars 2020. Il s’agit d’un événement artistique conçu, dirigé et réalisé par une équipe de femmes, immigrantes et allophones. Cet événement est ancré, d’une part, dans une démarche féministe empirique inductive visant la construction d’une scène sûre pour des artistes femmes immigrantes et allophones. D’autre part, il s’inspire de l’analyse préliminaire des données de ma recherche de doctorat sur les musicien·nes immigrant·es oeuvrant sur le marché de la « musique du monde » à Montréal. La construction d’une scène sûre pour ces femmes implique l’aménagement d’un espace dans lequel elles sont avant tout reconnues et appréciées en tant qu’artistes. En outre, l’analyse des données recueillies montre que le fait d’être à la fois artiste, femme, immigrante et allophone s’impose comme un quadruple défi. En s’inspirant de la notion d’« espace sûr », ce projet événementiel cherchait des réponses pragmatiques à deux problèmes vécus par les artistes femmes immigrantes allophones : leur sous-représentation dans le milieu artistique professionnel québécois et la langue en tant qu’obstacle à leur l’inclusion. Le Sarau résulte ainsi du travail collectif et de la volonté d’un groupe de femmes artistes, immigrantes et allophones entreprenant une démarche d’émancipation vis-à-vis leur propre invisibilité.
Keywords: 2000 à aujourd'hui; 2020-2029; DIG; amériques; approches et analyses; artistes féministes; arts; discipline; espace sécuritaire; femmes* artistes; femmes* immigrantes; intersectionnalité; invisibilité; inégalités; inégalités linguistiques; montréal; musique; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail